2010
DOI: 10.1021/ie100740d
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Degradation of MTBE by Pyrite-Activated Persulfate: Proposed Reaction Pathways

Abstract: This bench-scale study investigated the feasibility of activated persulfate (S(2)O(8)(2-)) oxidation of methyl tertbutyl ether (MTBE), using pyrite (FeS(2)) as the source of ferrous ion activators. Under the FeS(2)-activated S(2)O(8)(2-) condition, the sulfate free radical (SO(4)) is the predominant reactive species generated. The oxidation reactions were able to completely degrade MTBE when given sufficient doses of FeS(2) and S(2)O(8)(2-) and sufficient reaction time (e.g., 3 g FeS(2)/L and 5 g Na(2)S(2)O(8)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
46
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(47 citation statements)
references
References 32 publications
1
46
0
Order By: Relevance
“…The higher water solubility and persistence of MTBE can cause it to move faster than many other component of gasoline when released into aquifer. The toxicity of MTBE to animals and humans is well documented and it has been established that the MTBE is carcinogenic to animals (Belpoggi et al, 1995, Kamalan et al, 2009Liang et al, 2010). Franklin (2000) reported that MTBE has become one of the most problematic pollutants in urban soils and groundwater worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…The higher water solubility and persistence of MTBE can cause it to move faster than many other component of gasoline when released into aquifer. The toxicity of MTBE to animals and humans is well documented and it has been established that the MTBE is carcinogenic to animals (Belpoggi et al, 1995, Kamalan et al, 2009Liang et al, 2010). Franklin (2000) reported that MTBE has become one of the most problematic pollutants in urban soils and groundwater worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, persulfate was used as oxidant for in situ chemical oxidation (ISCO) technology to remedy groundwater and soil contaminants. Through thermal or chemical activation, persulfate can be transformed into sulfate radicals with more powerful oxidation potential to degrade refractory pollutants in groundwater or soil [17][18][19][20]. With success of ISCO soil and groundwater remediation, sulfate radical-based AOPs were emerging applied to the wastewater treatment purpose.…”
Section: Introductionmentioning
confidence: 99%
“…So far, the treatment of organic pollutants such as atrazine (Chan and Chu 2009), pharmaceuticals and personal care products (e.g. Chan et al 2010;Matta et al 2011;Nfodzo and Choi 2011;Rickman and Mezyk 2010), methyl tert-butyl ether (Liang et al 2010), polycyclic aromatic aromatic hydrocarbons (Wang et al 2008), phenols (e.g. Anipsitakis et al 2006;Yang et al 2008), and so on using SO 4 -Á has been reported.…”
Section: Introductionmentioning
confidence: 99%